2015
DOI: 10.1080/10286608.2015.1025386
|View full text |Cite
|
Sign up to set email alerts
|

Linking disaster resilience and sustainability

Abstract: Resilience and sustainability have both gained traction in civil engineering. There is significant overlap between both fields, but practitioners tend to remain confined to their niche. This paper clarifies the link between both fields, reflects on the underlying concepts, and identifies challenges and opportunities in understanding complex problems involving both resilience and sustainability. A conceptual framework is proposed for understanding resilience and sustainability together. The example of a coastal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Through the qualitative analysis of these papers, we can reveal that papers considering adoption are mostly either about adoption of different sustainable practices, policies or systems in agriculture [55][56][57], or they address questions of implementation of different sustainability and resilience policies and standards [58]. Studies on disaster resilience often concern a community level from different perspectives: for example, in engineering context [59], from a tourism development [60] or water supply contexts [61]. Despite certain peculiarities such as units of analyses, most of these studies agree that resilience and sustainability have a hierarchical relationship, where resilience is a part of sustainability: it is said that resilience is a "foundation" for sustainability [60], resilience is a "requirement" for urban system sustainability [62], or resilience is a necessary condition for sustainability [59].…”
Section: Resilience and Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Through the qualitative analysis of these papers, we can reveal that papers considering adoption are mostly either about adoption of different sustainable practices, policies or systems in agriculture [55][56][57], or they address questions of implementation of different sustainability and resilience policies and standards [58]. Studies on disaster resilience often concern a community level from different perspectives: for example, in engineering context [59], from a tourism development [60] or water supply contexts [61]. Despite certain peculiarities such as units of analyses, most of these studies agree that resilience and sustainability have a hierarchical relationship, where resilience is a part of sustainability: it is said that resilience is a "foundation" for sustainability [60], resilience is a "requirement" for urban system sustainability [62], or resilience is a necessary condition for sustainability [59].…”
Section: Resilience and Sustainabilitymentioning
confidence: 99%
“…Studies on disaster resilience often concern a community level from different perspectives: for example, in engineering context [59], from a tourism development [60] or water supply contexts [61]. Despite certain peculiarities such as units of analyses, most of these studies agree that resilience and sustainability have a hierarchical relationship, where resilience is a part of sustainability: it is said that resilience is a "foundation" for sustainability [60], resilience is a "requirement" for urban system sustainability [62], or resilience is a necessary condition for sustainability [59]. However, going deeper, Marchese et al [36] identified three possible frameworks for sustainability and resilience: (1) resilience as a component of sustainability;…”
Section: Resilience and Sustainabilitymentioning
confidence: 99%
“…Foremost, we have identified post-disaster pathways to resilience and sustainability of infrastructure systems, answering calls to bring specificity to these outcomes [64][65][66]. Our adaptation of current resilience indicators from developed countries (e.g., [67]) and sustainability indicators from development contexts (e.g., [27]) provide a useful tool to replicate assessing both of these outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Structures constructed in hazard prone regions need to be resilient to fulfill sustainability objectives (Wen et al, 2019; Zheng et al, 2018). Resilience and sustainability have vast similarities and should be used in an integrated perspective (Bocchini et al, 2014; Rodriguez-Nikl, 2015). Frameworks for the resilience and sustainability have been developed (Marchese et al, 2018) and studies are available incorporating sustainability in hazard prone regions (Asprone and Manfredi, 2015; Gencturk et al, 2016).…”
Section: Introductionmentioning
confidence: 99%